2011
DOI: 10.1128/aem.00172-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nitrogen-Incorporating Bacteria in Petroleum-Contaminated Arctic Soils by Using [ 15 N]DNA-Based Stable Isotope Probing and Pyrosequencing

Abstract: Arctic soils are increasingly susceptible to petroleum hydrocarbon contamination, as exploration and exploitation of the Arctic increase. Bioremediation in these soils is challenging due to logistical constraints and because soil temperatures only rise above 0°C for ϳ2 months each year. Nitrogen is often added to contaminated soil in situ to stimulate the existing microbial community, but little is known about how the added nutrients are used by these microorganisms. Microbes vary widely in their ability to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(85 citation statements)
references
References 46 publications
1
82
0
2
Order By: Relevance
“…This lack of success has been blamed on a failure to consider other environmental controls on hydrocarbon degraders (Thompson et al, 2005), and is not surprising in light of our results. Although hydrocarbon contamination can reduce the number of bacterial taxa in Arctic soils, there are still many that remain active (Bell et al, 2011), and competitive interactions between these remaining groups are likely to be governed by other environmental parameters. Our experimental setup controlled for contaminant composition, age and concentration, and found that differences in phylum-level community composition was best explained by soil organic matter content, especially in DSL-MAP soils.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This lack of success has been blamed on a failure to consider other environmental controls on hydrocarbon degraders (Thompson et al, 2005), and is not surprising in light of our results. Although hydrocarbon contamination can reduce the number of bacterial taxa in Arctic soils, there are still many that remain active (Bell et al, 2011), and competitive interactions between these remaining groups are likely to be governed by other environmental parameters. Our experimental setup controlled for contaminant composition, age and concentration, and found that differences in phylum-level community composition was best explained by soil organic matter content, especially in DSL-MAP soils.…”
Section: Discussionmentioning
confidence: 99%
“…The amendment that we selected is comparable in both type and concentration to those that have been used previously at hydrocarbon-contaminated Arctic sites (ThomassinLacroix et al, 2002;McCarthy et al, 2004;Greer, 2009;Bell et al, 2011). We expected that the success of hydrocarbon-degrading bacteria in disturbed soils would be governed by adaptations to the soil environment, and that we would observe clear differences in the relative abundance of hydrocarbon-degrading groups across soil gradients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amplification for 454 and for Ion Torrent sequencing was carried out using the Fusion protocol. For 454 sequencing, bacterial 16S rRNA gene amplification was carried out as described by Bell et al (1) using the forward primer Univ-9F (5=-GAG TTT GAT YMT GGC TC-3=) and the reverse primer BR534/18 (5=-ATT ACC GCG GCT GCT GGC-3=) (42) that were linked to Roche 454 adapters and the multiplex identifiers listed in Table S1 in the supplemental material. For Archaea 16S rRNA gene amplification, we used the following primers: forward primer 5=-CCA TCT CAT CCC TGC GTG TCT CCG ACT CAG XXX XXX XXX XAA TTG GAN TCA ACG CCG G-3=, first reverse primer 5=-CCT CTC TAT GGG CAG TCG GTG ATC GRC GGC CAT GCA CCW C-3=, and second reverse primer 5=-CCT CTC TAT GGG CAG TCG GTG ATC GRC RGC CAT GYA CCW C-3=, where the Xs represent the sample-specific multiplex identifier (listed in Table S1 in the supplemental material), the underlined sequences represent the template-specific sequences (958arcF, 1048arcRmajor, and 1048arcRminor, respectively, from reference 8), and the remaining sequence is the Ion Torrent adapter A (forward) and adapter trP1 (reverse).…”
Section: Methodsmentioning
confidence: 99%